Optimization of aromatic species in formulated fuel for simultaneous reduction of PM and NOx emissions from combustion engines. (August 2022) - Chapman, Jack; Singh, Paramvir; Kumar, Sudarshan; Khandelwal, Bhupendra
Abstract: A new integrated experimental technique is used to design viable and cleaner fuel blends with selective fuel contents. In diesel combustion engines, higher PM and NOx emissions are the major pollutants that need to be addressed simultaneously. The selection of fuel components based on emission formation tendencies is a promising approach to reduce these emissions. Aromatics highly affects the emission in diesel-fueled engines, especially PM. The present study provides a comprehensive knowledge database on a range of aromatics that need to be removed from the fuel during production processes for better performance and lower engine emissions. To investigate the effects of aromatic species and content on emissions, 16 different aromatic species were tested in 8, 13, and 18% volumetric concentrations in an alkane-based fuel. The experiments were conducted at 850 and 1500 rpm engine speed conditions. The ranking system was developed to rank the aromatics based on their overall performance in terms of PM and NOx emissions. The blend with 8% tert-butylbenzene showed a maximum PM reduction of 73.1% due to higher hydrogen atoms relative to carbon. Better atomization with higher volatility due to the lower density of this blend promoted oxidation rather than pyrolysis. NOx emissions were found to be maximum of 10.4% lower with 8% o-Xylene in the blend due to lower heat release rate. Improved heat distribution over the premixed and diffusion combustion modes due to this blend's optimum physical properties helped reduce the in-cylinder temperature. A consideration of equal weightage to NOx and PM emissions, 8% tert-butylbenzene is the most promising aromatic candidate for cleaner fuel production. Highlights: Fuel blends were formulated using 16 aromatic species. Potential approach of simultaneous reduction of PM and NOx is proposed. tert-butylbenzene was found to be most promising aromatic for future fuel formulation. Methylnapthalene should be avoided from fuel due to its higher PM emission formation tendency.